К ПРОБЛЕМЕ ОПРЕДЕЛЕНИЯ ПОНЯТИЯ ПРАВООХРАНИТЕЛЬНОЙ ДЕЯТЕЛЬНОСТИ ПО ПРОТИВОДЕЙСТВИЮ ПРАВОНАРУШЕНИЯМ В СФЕРЕ ХОЗЯЙСТВЕННОЙ ДЕЯТЕЛЬНОСТИ - Сугак, Алексей Викторович (SUPREMANCE OF LAW, 2018)
In the article, based on the analysis of the scientific views of scientists, the author’s definition of the concept of “counteracting offenses in the field of economic activity” is proposed. It is noted that law enforcement, being a rather complex and multidimensional phenomenon, in the context of the implementation by competent subjects of countering offenses in the field of economic activity, has a number of characteristic features. A list of these features is given. The classification of law enforcement activities to combat offenses in the field of economic activity has been carried out.
Keywords: law enforcement; counteraction; offense; economic activity; classification